2015
DOI: 10.1007/s00425-015-2420-3
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale comparative phosphoprotein analysis of maize seedling leaves during greening

Abstract: MAIN CONCLUSION : Large-scale comparative phosphoprotein analysis in maize seedlings reveals a complicated molecular regulation mechanism at the phosphoproteomic level during de-etiolation. In the present study we report a phosphoproteomic study conducted on Zea mays etiolated leaves harvested at three time points during greening (etiolated seedlings and seedlings exposed to light for 6 or 12 h). We identified a total of 2483 phosphopeptides containing 2389 unambiguous phosphosites from 1339 proteins. The abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…The distribution of seed proteins’ subcellular localization varies with different developmental stages, seed structure, etc. In many studies on seed germination, the “nucleus” is the subcellular structure with the most protein species, due to vigorous cell division activity (Ning et al, ; Wang et al, ). Unlike the developing seeds, The TBS samples in this study were dormant seeds in storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of seed proteins’ subcellular localization varies with different developmental stages, seed structure, etc. In many studies on seed germination, the “nucleus” is the subcellular structure with the most protein species, due to vigorous cell division activity (Ning et al, ; Wang et al, ). Unlike the developing seeds, The TBS samples in this study were dormant seeds in storage.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of seed proteins' subcellular localization varies with different developmental stages, seed structure, etc. In many F I G U R E 2 The mass error (a) and length (b) distribution of the identified peptides from buckwheat seeds; sequence coverage (c) and molecular weight (d) distribution of the identified proteins from tartary buckwheat seeds studies on seed germination, the "nucleus" is the subcellular structure with the most protein species, due to vigorous cell division activity (Ning et al, 2016;Wang et al, 2017). Unlike the developing seeds, The TBS samples in this study were dormant seeds in storage.…”
Section: Subcellular Localization Of Tbs Proteinsmentioning
confidence: 99%
“…It has been reported that more than 1000 genes are modulated at the transcript level during the greening of Arabidopsis and Rice etiolated seedlings17. There have been so many studies on greening, mainly focused on gene expression, particularly of photosynthetic genes, and on modulation of the corresponding protein levels18. In addition, a proteomic analysis that focused on light-induced development of chloroplasts from etioplasts was also performed on rice seedlings during greening19.…”
mentioning
confidence: 99%
“…To perform a deep analysis of the maize proteome and phosphoproteome during de-etiolation, the first leaves of etiolated 7-day-old maize seedlings (B73 inbred) were illuminated with white light and harvested at 0 h, 1 h, 6 h and 12 h for mass spectrometry analysis ( Figure 1 ). We chose these samples for analysis because in our previous studies [25, 31, 32] we found that the first leaves of 7-day-old etiolated maize seedlings showed no significant changes in growth compared with light-grown seedlings when subjected to illumination for 12 hours, and few proteins involved in development and growth were found to be differently expressed when comparing the proteomes of etiolated and normal leaves. Moreover, the etiolated leaves turned green after 12 hours of illumination, which indicated that processes related to greening in leaves were completed.…”
Section: Resultsmentioning
confidence: 99%
“…The completion of the B73 maize genome [26] has facilitated the use of large-scale transcriptome and proteome data to reveal the mechanisms underlying various maize developmental and physiological processes. For example, researchers have created large data resources for C4 photosynthesis research, including complementary RNA-seq [27], proteomics [28, 29], and phosphoproteomics [30, 31] data for a developmental gradient of the maize leaf. In these studies, the mRNA and protein contents at successive stages of photosynthetic development were analyzed.…”
Section: Introductionmentioning
confidence: 99%